Small Interfering RNA Efficiently Suppresses Adhesion Molecule Expression on Pulmonary Microvascular Endothelium - Tobias Walker; Julian Siegel; Andrea Nolte; Silke Hartmann; Angela Kornberger; Volker Steger; Hans-Peter Wendel (Journal of Nucleic Acids)
Background. Adhesion molecules are known to influence postoperative organ function, they are hardly involved in the inflammatory response following the ischemia-reperfusion injury. We sought to investigate the potency of small interfering RNAs to suppress adhesion molecule expression in human pulmonary microvascular endothelial cells. Methods. Human lung microvascular endothelial cells were transfected with specific siRNA followed by a stimulation of the cells with an inflammatory cytokine. Adhesion molecule expression was determined by FACS-analysis, and reduction of intracellular mRNA was determined by qRT-PCR. Furthermore, the attachment of isolated neutrophils on the endothelial layer was determined after siRNA transfection. Results. In summary, siRNA transfection significantly decreased the percentage positive cells in a single cocktail transfection of each adhesion molecule investigated. Adhering neutrophils were diminished as well. Conclusion. siRNA might be a promising tool for the effective suppression of adhesion molecule expression on pulmonary microvascular cells, potentially minimizing leukocyte-endothelial depending interactions of a pulmonary allograft.